Periphrases of St. Petersburg in Contemporary Media Discourse: A Pragmatic Perspective - E. A. Bespalova (Научный диалог)
This article examines the distinctive features of periphrastic nominations of St. Petersburg in modern media texts, as represented in the newspaper corpus of the Russian National Corpus. The study aims to identify the current meanings and functional capabilities of these units within media discourse. The relevance of this research is underscored by its linguo-pragmatic focus, emphasizing the importance of studying toponymic periphrases as a means of influencing readers and as a significant linguistic resource for journalists. It is demonstrated that figurative nominations of St. Petersburg are actively employed in media texts, assisting authors in marking the location of events, shaping perceptions of the city, providing evaluations, and highlighting necessary meanings. The author identifies several functions of periphrases, including references to historical epochs, means of poeticization, positive evaluation, substantive characterization, and assessing contemporary events through historical associations; the synonymous replacement of a toponym with a figurative expression allows for the avoidance of repetition. In newspaper texts, the semantic scope of toponymic periphrases varies, with an observable expansion of meanings and the development of metaphorical imagery. The use of periphrases confirms the relevance of the topic of comparing the two capitals for native speakers. Examples are provided illustrating the construction of puns using St. Petersburg periphrases based on homonymy, polysemy, antonymy of statement components, as well as structural-semantic transformations of periphrastic constructions.